1998
DOI: 10.1520/jfs16101j
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and the Law Reconsidered: Psychological Syndromes and Profiles

Abstract: Recently, a new concept of behavior and the law has emerged which looks beyond the defendant's satisfaction of the elements which define the charge. This formulation, which considers not simply the objective facts but motive, intent, and circumstance, has marked a legal shift from diminished capacity to diminished responsibility. Still in evolution, this trend has challenged the relationship between law and the behavioral sciences, and prompted serious reconsideration of the role of each. This paper examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is important that psychiatrists are clear about the distinction between clinical and forensic roles (29). It has been suggested that the concept of diminished capacity should be replaced by the concept of diminished responsibility, thus not only considering the objective facts but also motives, intent and circumstances (30).…”
Section: Justicementioning
confidence: 99%
“…It is important that psychiatrists are clear about the distinction between clinical and forensic roles (29). It has been suggested that the concept of diminished capacity should be replaced by the concept of diminished responsibility, thus not only considering the objective facts but also motives, intent and circumstances (30).…”
Section: Justicementioning
confidence: 99%